The role of interoceptive awareness in social anxiety disorder – results of an internet-based CBT-manualized therapist delivered group-treatment - I. Schmalbach; K. Petrowski (BMC Psychology)
Abstract Background Interoception, the process of detecting internal bodily signals, is linked to emotional regulation and mental health. Dysregulated interoceptive awareness (IAw) is associated with psychopathology, including social anxiety disorder (SAD), where internal cues influence negative self-perception and anxiety. While internet-based cognitive behavioral therapy (ICBT) offers an effective and more accessible treatment option, experimental treatment outcomes related to IAw and specific to SAD are rare. Hence, the present study aims to assess IAw and SAD symptom changes post-ICBT group therapy and determine whether IAw serves as a predictor of treatment outcome. Method We collected data of N = 47 participants with SAD via online advertisement and outpatients of the University Hospital Clinic between November 2021 - May 2025. Participants met SAD criteria and underwent psychological assessments regarding IAw (via the Multidimensional Assessment of Interoceptive Awareness-2; MAIA-2) and symptoms of social anxiety (using the Liebowitz Social Anxiety Scale; LSAS) measured pre- and post-treatment. SAD participants received a three-month, therapist-delivered, internet-based CBT group psychotherapy (ICBT), focusing on behavioral experiments, psychoeducation, cognitive restructuring, and relapse prevention. Results The study revealed significant reductions in SAD symptoms and improvements in interoceptive awareness dimensions as indicated by subscales of the MAIA-2 (i.e., Attention Regulation, Self-Regulation). Changes in Attention Regulation and Self-Regulation predicted a significant portion of variation in treatment outcome for SAD. Baseline values of IAw related to Not-Distracting and Not-Worrying also predicted treatment change. Combined predictors significantly predicted improvement in SAD symptomatology. Conclusion This study provides strong evidence for the efficacy of therapist-delivered ICBT in reducing social anxiety symptoms while enhancing interoceptive capacities. Baseline Not-Distracting and Not-Worrying predicted better outcomes, highlighting their prognostic value. Improvements in Attention and Self-Regulation further contributed to symptom reduction, suggesting a key mechanism of action. These findings underscore the potential for interoceptive-focused interventions to optimize SAD treatment and highlight the accessibility of ICBT as a scalable therapeutic option.